Ecotoxicity of cerious nanoparticles in different organisms: a review - Druzian, Daniel Moro; Oviedo, Leandro Rodrigues; Loureiro, Sthéfany Nunes; Da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Cerium oxide nanoparticles (CeO2-NPs) are widely utilized in several areas such as; engineering, energy and biomedicine mainly due to the redox properties (Ce+3,+4,+5) indicating a reducing potential to reduce oxidative stress in organisms. Thus, conflicting articles on the ecotoxicity of CeO2-NPs have been published in recent years, demonstrating a protective effect of oxidation on organisms and high toxicity. To analyze and investigate the possible reasons, a comprehensive study of CeO2-NPs was realized out with several variables and aquatic, terrestrial and flyers organisms. Also, CeO2-NPs did not demonstrate a high ecotoxicity against different organisms (aquatic, terrestrial and flyers) compared to the current permitted legislation. At the same time, microorganisms such as algae (Chlamydomonas reinhardtii and Pseudokirchneriella subcapitata) showed an inhibitory effect on growth, possibly due to the redox properties of CeO2-NPs causing an imbalance of reactive oxygen species in the solutions. Moreover, factors and parameters that affect the ecotoxicity of CeO2-NPs are denoted, such as; concentration, exposure time, organisms, solution pH and properties (surface area and positive or negative charge). It is assumed that CeO2-NPs will be more used and investigated and analyzed in aquatic, terrestrial and flyers environments using different organisms and comparing them, as well as using tracking methods to understand and study ecotoxicity processes involving metallic nanoparticles and organisms.